Effectiveness of Digital Sound Therapy (DST) in Reducing Postoperative Pain Intensity Among Adult Surgical Patients - Ariani, Sri Purwanti; Ernawati, Ernawati; Yuhansyah, Yuhansyah; Rapika, Rapika (Chakra Brahmanda Lentera Institute, 2026)
Background: Postoperative pain remains one of the most common complications experienced by patients after surgery and may delay recovery, increase the risk of complications, and prolong hospitalization. Non-pharmacological interventions are increasingly recommended as complementary approaches to postoperative pain management. Despite growing evidence supporting audio-based interventions for pain management, evidence regarding the effectiveness and clinical implementation of Digital Sound Therapy (DST) among postoperative patients in Indonesian hospitals remains limited. Therefore, this study aimed to evaluate the effectiveness of Digital Sound Therapy (DST) in reducing postoperative pain intensity among adult surgical patients. Methods: A quasi-experimental pretest–post-test control group study was conducted and reported according to the TREND guidelines. Sixty postoperative patients were selected through purposive sampling and assigned to an intervention group (n = 30) and a control group (n = 30). The independent variable was Digital Sound Therapy (DST), whereas the dependent variable was postoperative pain intensity. Pain intensity was measured using the Numeric Rating Scale (NRS) four hours after surgery (pretest) and immediately after a 20–30-minute Digital Sound Therapy (DST) intervention (post-test). The control group received standard postoperative nursing care without additional audio therapy. Data were analysed using the Wilcoxon Signed-Rank Test. Results: Baseline demographic characteristics showed that most participants in the intervention group were aged 19–44 years (73.4%), female (63.3%), employed in the private sector (56.7%), and had completed senior high school education (46.6%). Before the intervention, 30.0% of patients reported mild pain, 53.3% moderate pain, and 16.7% severe pain. Following Digital Sound Therapy (DST), the proportion of patients reporting mild pain increased from 30.0% to 86.7%, while moderate pain decreased from 53.3% to 13.3%, and severe pain was eliminated. In contrast, most patients in the control group continued to experience moderate pain (70.0%) after the second assessment. The reduction in postoperative pain intensity following Digital Sound Therapy (DST) was statistically significant (p = 0.005). Conclusion: Digital Sound Therapy (DST) effectively reduces postoperative pain intensity and should be considered as a complementary component of multimodal postoperative pain management in nursing practice. Further multicenter studies with larger sample sizes are recommended to confirm its effectiveness and support broader clinical implementation